Genetic Characterization of Enterovirus A71 Circulating in Africa - Fernandez-Garcia, Maria Dolores; Volle, Romain; Joffret, Marie-Line; Sadeuh-Mba, Serge Alain; Gouandjika-Vasilache, Ionela; Kebe, Ousmane; Wiley, Michael R.; Majumdar, Manasi; Simon-Loriere, Etienne; Sakuntabhai, Anavaj; Palacios, Gustavo; Martin, Javier; et al. (Emerging infectious diseases, 2018)
We analyzed whole-genome sequences of 8 enterovirus A71 isolates (EV-A71). We confirm the circulation of genogroup C and the new genogroup E in West Africa. Our analysis demonstrates wide geographic circulation and describes genetic exchanges between EV-A71 and autochthonous EV-A that might contribute to the emergence of pathogenic lineages.